Letter : Relief for Spain - Davison, W.
012a-0010-001 The National Union of Blastfurnacemen, Ore Miners, Coke Workers and Kindred Trades. Thomas McKenna, O.B.E. General Secretary. 93, Borough Road West, Middlesbrough 25th Nov. 1938 Mr. H. V. Tewson, Assistant Secretary, The Trades Union Congress, Transport House, Smith Square, London S.W.1 Thomas McKenna, OBE General Secretary. Dear Mr.Tewson, Relief for Spain We thank you for your letter of yesterday's date containing information re the above. Mr. McKenna left yesterday for a meeting of the Metalworkers International in Switzerland, but we are forwarding your letter on to him to-day so that it will be in his possession in good time for the meeting. Yours faithfully, W. Davidson 292/946/12a/10